Efficient Procedure for High-Yield Synthesis of 4-Substituted 3,5-Dinitropyrazoles Using 4-Chloro-3,5-dinitropyrazole - Dalinger, Igor L.; Vatsadze, Irina A.; Shkineva, Tatyana K.; Popova, Galina P.; Shevelev, Svyatoslav A. (Synthesis, 2012)
The transformations of readily available 4-chloro-3,5-dinitropyrazole and its N-methylated derivative under the action of anionic S-/O-nucleophiles and neutral N-nucleophiles were studied. Independent of the substrate’s charge (anionic, R = H, or neutral, R = Me), the nucleophilic substitution proceeds exclusively at position 4 replacing the chlorine nucleofuge. As a result of this study, the effective synthetic method for the preparation of 4-substituted 3,5-dinitropyrazoles via the nucleophilic substitution in 4-chloro-3,5-dinitropyrazole was elaborated.
Keywords: pyrazoles; nitropyrazoles; 3,5-dinitropyrazoles; nucleophiles; nucleophilic substitution; selective substitution